Numerical treatment for fluidic system of activation energy with non-linear mixed convective and radiative flow of magneto nanomaterials with Navier’s velocity slip - Iftikhar Uddin; Rizwan Akhtar; Muhammd Abdul Rehman Khan; Zhu Zhiyu; Saeed Islam; Muhammad Shoaib; Muhammad Asif Zahoor Raja (AIP Advances, 2019)
A novel application of Lobatto IIIA computing solver is presented for the solution of nanofluidic Buongiorno model in the porous space. Incompressible electrically conducting fluid mixed with nanomaterial is considered. Flow expression is modelled via nonlinear mixed convection and Navier’s slip condition. Activation energy, Joule heating and non-liner thermal radiation characterise the heat/mass transport. The governing PDEs of the considered problem are transformed into an equivalent system of ODEs using similarity variables. The resulting system is solved numerically by exploiting the strength of Lobatto IIIA computing solver. Numerical and graphical illustrations are utilized to interpret the behaviour of sundry physical parameters on velocity, concentration and temperature profiles. Skin friction, temperature and concentration gradients for different scenarios of embedding variables are tabulated and analysed. Furthermore, numerical data for mesh points, error analysis, ODEs and boundary conditions evaluation are also displayed. Our computed analysis indicates that velocity of nanofluid increases for large value of slip parameter while it decreases with the increase of porosity parameter. In addition, concentration distribution is decaying and increasing functions of chemical reaction and activation energy parameters respectively.